Adicción a Redes Sociales y Riesgo de Desarrollar Trastornos Alimenticios en Adolescentes. Unidad Educativa La Condamine. Pallatanga, 2022 - Castillo Gonzales, Mayra Elizabeth (2022)
ABSTRACT: The present investigation had as objective to analyze the addiction to social networks and the risk of developing eating disorders in adolescents of the Educational Unit "La Condamine" of the Pallatanga canton. The methodology used was of a quantitative, documentary and bibliographic type, of a non-experimental and cross-sectional design and of a descriptive and correlational level. The study sample comprised of 227 students whose ages ranged from 12 to 18 years. The information was obtained from the anonymous database of the educational institution of the results of the Addiction Scale to Social Networks (ARS) and the Eating Attitudes Test (EAT-26). Based on the most relevant results, they point out that in the dimensions of addiction to networks, in the lack of personal control in the use of social networks, 48.9% present a medium level, in the excessive use of networks social, 43.6% denote a medium level. Regarding the variable risk of developing eating disorder, it was found that 56.8% of the population presented a higher risk and 43.2% lower severity. Therefore, to the relationship between the variables raised, a statistically low positive significant relationship was identified with (<0.01), which indicates that the greater the addiction to social networks, the greater the risk of developing eating disorder. Keywords: Addiction to social networks, adolescents, eating disorders.